How do Para swimmers respond physiologically and cognitively when watching their performance at the Paralympic Games? A Case Study - Bardella Soares, Bruna; Winckler, Ciro (Cuadernos de Psicología del Deporte, 2023)
The aim of this study was to analyse the cognitive and physiological activation response of Paralympic swimmers (n= 12) when watching the recording of their events at the 2016 Paralympic games. The methodological design of the study was cross-sectional and carried out in two stages. The video contained three moments: baseline (BL), neutral video (NV) and Paralympic Games video (GAMESV). During the tests, Heart Rate Variability (HRV) and Electrodermal Activity (EDA) were analysed as a way to evaluate physiological activation. Before and after the video, cognitive activation data (State-Trait Anxiety Inventory) was collected. It was observed a significant reduction in the meantime of heartbeats and an increased conductance data in relation to NV×GAMESV, demonstrating physiological activation. However, no significant differences in cognitive activations were observed. While the use of videos in the psychological and sporting scope may be explored, certain weightings should be considered, knowing that their content may elicit positive or negative responses to performance.